Enhancing Junior High School Students' Mathematical Critical Thinking Ability Through the Discovery Learning Model Assisted with Learning Videos - Pasaribu, Novelia Finenes; Fisher, Dahlia; Saputra, Jusep; Sahrudin, Asep (Universitas Sarjanawiyata Tamansiswa, 2023)
Critical thinking ability is one of the higher orders thinking skills that is highly needed in 21st-century learning. One learning model that can develop and enhance students' necessary thinking skills, especially in learning mathematics, is the Discovery Learning model. Using video media in learning can motivate and assist students in learning mathematics. This study aimed to determine the increase in students' mathematical critical thinking skills through the Discovery Learning model helped by teaching videos. The research method used is quasi-experimental. The samples in this study were students at class VII Bandung National Middle School. The sample was selected by purposive sampling technique. This research shows that students who get the Discovery Learning model assisted by video-assisted learning have a higher mathematical critical thinking ability than those who get conventional models.